Doing research - Thomas, Gary (Palgrave Macmillan, 2015)
This concise guide equips undergraduate students with the basic knowledge for doing research. Providing direct, practical advice, this well-presented book covers planning, groundwork, research design, fieldwork, analysis and writing up.